Development of Network Infrastructure Monitoring System at Vocational High School Using MikroTik and Telegram Integration - Pratama, Bayu; Zulhendra; Hadi, Ahmaddul; Mursyida, Lativa (Sagamedia Teknologi Nusantara, 2024)
This study aimed to develop a monitoring system for the computer network infrastructure at SMKN 7 Sijunjung. The system was designed to provide real-time monitoring of traffic, activity logs, and connected user devices on the MikroTik router; additionally, the application integrated notifications through the Telegram service to offer prompt information regarding network disruptions. The design methodology employed was PPDIOO (prepare, plan, design, implement, operate, and optimize). The system is implemented using a combination of hardware and software, including the utilization of the CodeIgniter framework for the user interface (UI). System testing was conducted using the BlackBox method to evaluate the functionality of the application comprehensively. The test results confirm that the application effectively monitored the network and promptly notified us of its status. However, there were certain challenges identified during testing, such as problems with online connectivity to the MikroTik router and limitations in database storage. The proposed solutions include activating the VPN on MikroTik and enhancing database storage capacity. This research contributes to the development of computer network infrastructure-monitoring systems in educational environments. These findings will lay the groundwork for other educational institutions to enhance the efficiency of network monitoring and maintenance in schools.